Hubungan Indeks Massa Tubuh Dengan Tekanan Darah Pada Orang Dewasa di Desa Rowokembu Kabupaten Pekalongan - Putri, Risma Amanda; Wiwiek Natalya (LPPM UNIKAL, 2025)
Introduction: The prevalence of hypertension among people aged ≥18 years in Indonesia is 30.8%, with the majority being adults. This study aimed to determine the correlation between body mass index and blood pressure in adults. Methods: This was a quantitative study with a correlational design using a cross-sectional approach. The sample consisted of 87 adults in Rowokembu Village, Pekalongan Regency, selected by cluster random sampling. The measurement tools consisted of a stadiometer, a weighing scale, and a digital sphygmomanometer. Data analysis was performed using the Spearman rank test. Results: The findings showed that the mean body mass index was 22.890, the mean systolic blood pressure was 119.24, and the mean diastolic blood pressure was 81.33. The Spearman rank test showed a p-value of 0.000 < α (0.05) for the correlation between body mass index and systolic blood pressure, while the correlation between body mass index and diastolic blood pressure produced a p-value of 0.003 < α (0.05). These results indicate a significant correlation between body mass index and blood pressure in adults in the village. Conclusion: There is a correlation between body mass index and blood pressure in adults in Rowokembu Village, Pekalongan Regency. Health workers are advised to provide counselling on the importance of maintaining an ideal body weight to prevent high blood pressure. Keywords: Adults, blood pressure, body mass index